In the Park, Port of Spain - (:unkn) unknown (My University, 2010)
This postcard features what might be beggars sitting under a tree in Marine Square, Port of Spain renamed Independence Square circa 1961. Two sailors are walking by on the opposite side of the road.
Colour: Black and white; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Beggars--Trinidad and Tobago; Poor--Trinidad and Tobago; Plazas--Trinidad and Tobago; Sailors--United States; Independence Square (Port of Spain); Marine Square (Port of Spain)